(untitled) (Baltic Journal of Sport and Health Sciences, 2011)
Research background and hypothesis. While for some authors team sport players should have a high VO 2 max, we hypothesize that there exist a non-linear relationship between VO 2 max and basketball performance. Research aims. Research aims were to study the correlation between basketball performance and VO 2 max in young elite basketball players and the effects of VO 2 max training on performance. Research methods. In the ﬁ rst study, 67 high-level young basketball players performed a shuttle-run test (SRT) to measure their VO 2 max. Competition performance assessed through statistics ratings of 5 matches was determined for all players. The correlation between VO 2 max and performance was calculated. In the second study, the VO 2 max and the competition performance of 34 high-level young male players was assessed as in the ﬁ rst study. The sample was divided into control and experimental groups, which trained their VO 2 max. At the end of the training period all participants repeated the SRT. The results of 4 games played before the ﬁ rst test and 4 games played after the second test (against the same opponents) were compared in both groups. Research results. In the ﬁ rst study we found a correlation of VO 2 max with steals in both groups. In the second study, the experimental group increased their VO 2 max and steals per game, but they decreased free throw per game and free throw percentage. Discussion and conclusions. No correlation was found between VO 2 max and competitive performance in this study, and increased VO 2 max had no effect on most of the studied variables. The data therefore suggest a non-linear relationship between VO 2 max and basketball performance. Keywords: aerobic capacity, basketball performance, non-linear relationship.